IPTEKS PERLAKUAN AKUNTANSI KREDIT USAHA RAKYAT PADA PT. BANK MANDIRI (PERSERO) TBK. AREA MANADO - Sembiring, Maya; Suwetja, I Gede (Universitas Sam Ratulangi, 2018)
PT. Bank Mandiri (Persero) Tbk. It is one of the agencies that implements the People's Business Credit (KUR) program in providing loans to parties Micro, Small and Medium Enterprises (UMKM) who want to open a business. Accounting treatment in the People's Business Credit (KUR) program is very important for creditors and prospective debtors because with Accounting both parties can plan business financial properly. The purpose of this study was to analyze the accounting treatment of people's business credit at PT. Bank Mandiri (Persero) Tbk. Manado area. Based on the results of the Accounting research applied by Bank Mandiri to Micro, Small and Medium Enterprises (UMKM) who want to open a business. Accounting treatment in the People's Business Credit (UMKM)is income statement. The Income statement is one of the conditions for prospective debtors so that credit disbursement can be disbursed because the income statement contains information about the income, expenses and net income received by the company in a period of one month. So that the results of the profits obtained by Bank Mandiri can see how much credit limit the company can give to prospective debtors. Bank Mandiri applies DSR as one of the conditions for calculating the approved limit. DSR is a ratio that calculates how much income is obtained by prospective debtors to pay the total debt.Keywords : Kredit Usaha Rakyat (KUR), Usaha Mikro Kecil dan Menengah (UMKM), income statement, debt to service ratio (DSR)